Denudation history of the Bocaina Plateau, Serra do Mar, southeastern Brazil: Relationships to Gondwana breakup and passive margin development - Hiruma, Silvio T.; Riccomini, Claudio; Modenesi-Gauttieri, May C.; Hackspacher, Peter Christian [UNESP]; Hadler Neto, Julio C.; Franco-Magalhaes, Ana O. B. [UNESP] (Elsevier B.V., 2010)
The Bocaina Plateau, which is situated on the eastern flank of the continental rift of southeastern Brazil, is the highest part of the Serra do Mar. Topographic relief in this area is suggested to be closely related to its complex tectono-magmatic evolution since the breakup of Western Gondwana and opening of the South Atlantic Ocean. Apatite fission track ages and track length distributions from 27 basement outcrops were determined to assess these hypotheses and reconstruct the denudation history of the Bocaina Plateau. The ages range between 303 +/- 32 and 46 +/- 5 Ma, and are significantly younger than the stratigraphic ages. Mean track lengths vary from 13.44 +/- 1.51 to 11.1 +/- 1.48 mu m, with standard deviations between 1.16 and 1.83 mu m. Contrasting ages within a single plateau and similar ages at different altitudes indicate a complex regional tectonothermal evolution. The thermal histories inferred from these data imply three periods of accelerated cooling related to the Early Cretaceous continental breakup, Early Cretaceous alkaline magmatism, and the Paleogene evolution of the continental rift of southeastern Brazil. The oldest fission track ages (>200 Ma) were obtained in the Serra do Mar region, suggesting that these areas were a long-lived source of sediments for the Parana, Bauru, and Santos basins. (C) 2010 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: Denudation; Apatite fission track analysis; Bocaina Plateau; Passive continental margin; Southeastern Brazil